The Naval Aviation Supply Office Inventory Retrieval System—A Case Study in File Automation - Zimmerman, Barry; Lefkovitz, David; Prywes, Noah S. (Management Science, 1964)
This article describes the case history of the pilot mechanization of files at the Naval Aviation Supply Office. The system described retrieves information on a real-time basis from a large file of technical and inventory data stored on magnetic disk memory. A feature of the system is the use of the Multi-List technique which stores an addressing index in the form of trees that provide access to the main file. The main file may be accessed by many different types of descriptors. Input to the file is via magnetic tape, console inquiry, or remote interrogation station. File and tree construction, the use of linkages between items to form lists, and the executive routine are described.